Victim empathy deficits among sex offenders in Kajang Prison - Zaizul Ab. Rahman; Ab. Aziz Mohd. Zain; Fakhrul Adabi Abdul Kadir (Penerbit Universiti Kebangsaan Malaysia, 2013)
A high incidence of rape and incest is emerging in Malaysia, especially among middle and lower income families in remote rural and coastal communities.The researchers have abided by the legal definition of rape in Malaysia, in which rape is defined as the forced penetration of a penis into vagina. This means that cases or forced oral or anal penetration (generally categorized by the police, courts etc as ‘molest’ or ‘outrage of modesty’), or in which that attacker used an object such a stick to rape the victim (which in many countries would be classified as rape. Incest, defined as sexual relationship between closely related persons forbidden by law to marry, incest , however is more often a case of the male adult forcing himself on a minor relative, in many cases a child. The impact of rape and incest is widespread, affecting the victim, family, friends, and society. While the prevalence of them has become part of Malaysian consciousness in recent years, the Malaysian remains less aware that a large number of these abusive acts are perpetrated within familial relationships. These cases are some of the most extreme examples of violence against girls and women (VAW). So, shocking and disturbing were they that they grabbed headlines and sparked public outrage throughout the nation. Malaysia Police statistic for 2006 show that 581 cases of rape from January to April that increased around 127 cases from last year. The trauma of victims has been such that many have attempted suicide or run away. The most visible emotional scar, often for life, is the victim’s difficulty in trusting and building relationships with other people. Most important, society must report and act on such happenings. But sex is not a subject that easily discussed in Malaysia even between husband and wife.